Development and application of a physically based landscape water balance in the SWAT model - White, E.D.; Easton, Z.M.; Fuka, D.R.; Collick, A.S.; Adgo, E.; McCartney, Matthew P.; Awulachew, Seleshi Bekele; Selassie, Yihenew G.; Steenhuis, Tammo S. (Wiley, 2011)
Watershed scale hydrological and biogeochemical models rely on the correct spatial-temporal prediction of processes governing water and contaminant movement. The Soil and Water Assessment Tool (SWAT) model, one of the most commonly used watershed scale models, uses the popular curve number (CN) method to determine the respective amounts of infiltration and surface runoff. Although appropriate for flood forecasting in temperate climates, the CN method has been shown to be less than ideal in many situations (e.g. monsoonal climates and areas dominated by variable source area hydrology). The CN model is based on the assumption that there is a unique relationship between the average moisture content and the CN for all hydrologic response units (HRUs), and that the moisture content distribution is similar for each runoff event, which is not the case in many regions. Presented here is a physically based water balance that was coded in the SWAT model to replace the CN method of runoff generation. To compare this new water balance SWAT (SWAT-WB) to the original CN-based SWAT SWAT-CN), two watersheds were initialized; one in the headwaters of the Blue Nile in Ethiopia and one in the Catskill Mountains of New York. In the Ethiopian watershed, streamflow predictions were better using SWAT-WB than SWAT-CN [Nash-Sutcliffe efficiencies (NSE) of 0?79 and 0?67, respectively]. In the temperate Catskills, SWAT-WB and SWAT-CN predictions were approximately equivalent (NSE >0?70). The spatial distribution of runoff-generating areas differed greatly between the two models, with SWAT-WB reflecting the topographical controls imposed on the model. Results show that a water balance provides results equal to or better than the CN, but with a more physically based approach.